KEWENANGAN KOMISI PENGAWAS PENYIARAN DALAM MENJAGA NETRALITAS MEDIA TELEVISI DALAM PILKADA DKI JAKARTA TAHUN 2017 - Martono, Joko; Annurdi, Annurdi (Faculty of Law, Tanjungpura University, 2018)
Television as one of mass media, other than as a source of information for the public, in the other hand can be used also as a promotional media especially in this case during the election of regional head. The role of television as a source of information, can affect a person (voter) in determining his choice, so that the television stations should be able to maintain its neutrality. However, the existence of television stations that favor one of the candidates is very likely to occur especially in the election of regional heads that attracted a lot of public attention, one of them in the election of regional head in Jakarta. This research type is normative juridical research, and the data used for this research are some legislations, documents and books relating elections and broadcasting.The result of this research revealed that there is still any television stations that favor to one of the candidates in political contestation (election of regional head) in Jakarta, so that those television stations got warning from Indonesian Broadcasting Commission (KPI), but the current legislation regarding broadcasting was deemed necessary to revision regarding KPI's authority as well as on tougher punishment on television providers that proven to have committed such violations, so that the imposition of sanctions can be more effective.